HETEROGENEITY OF JKN-PBI’S IMPACT ON HOUSEHOLD OUT-OF-POCKET HEALTH EXPENDITURES IN INDONESIA - Indriani, Ria; Wahyuni, Ribut Nurul Tri (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: The National Health Insurance-Contribution Assistance Recipients (JKN-PBI) participants in Indonesia tended to increase. However, out-of-pocket (OOP) health expenditures among participants did not significantly decrease. This phenomenon may have occurred because the impact of this program on OOP health expenditures varied by household group. Aims: This study investigated the heterogeneity impact of the JKN-PBI program across per capita expenditure quartiles and residential regions in 2024. Methods: The study used data from BPS-Statistics Indonesia. Because the determination of JKN-PBI program recipients was endogenous, this study used the Inverse Propensity Score Weighting (IPW) model. Tobit regression was also applied to accommodate the OOP health expenditure reported as a zero value. Results: Participation in JKN-PBI significantly reduced OOP health expenditures. More nominal reductions occurred in higher quartiles, whereas proportional reductions occurred in lower quartiles.  This outcome indicated that households in the lower quartiles obtained greater health service advantages relative to households in the higher quartiles.  The reduction in OOP health expenditure share was also greater in rural areas. Conclusion: The government must prioritize this program in rural regions and low-income households. In addition, the government needs to identify healthcare service needs by regions and income groups so that the use of the JKN-PBI card is more optimal. Keywords: National Health Insurance Program, Out-of-Pocket Expenditure, Heterogeneous Impact, Inverse Propensity Score Weighting, Tobit Regression